2012
DOI: 10.1155/2012/584831
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of Fetal Programming in Hypertension

Abstract: Events that occur in the early fetal environment have been linked to long-term health and lifespan consequences in the adult. Intrauterine growth restriction (IUGR), which may occur as a result of nutrient insufficiency, exposure to hormones, or disruptions in placental structure or function, may induce the fetus to alter its developmental program in order to adapt to the new conditions. IUGR may result in a decrease in the expression of genes that are responsible for nephrogenesis as nutrients are rerouted to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…The relative protection of females against the unfavorable outcome of fetal programming, has been attributed to the effects of sex hormones [16,47]. In fact, there is evidence that testosterone is elevated in male rats exposed to IUGR and hypertension is abolished by castration [48].…”
Section: Discussionmentioning
confidence: 99%
“…The relative protection of females against the unfavorable outcome of fetal programming, has been attributed to the effects of sex hormones [16,47]. In fact, there is evidence that testosterone is elevated in male rats exposed to IUGR and hypertension is abolished by castration [48].…”
Section: Discussionmentioning
confidence: 99%
“…Environmental perturbations during pregnancy predispose offspring to altered vascular function, leading to hypertension [ 6 , 7 , 8 , 9 ] and cardiovascular disease later in life [ 10 ]. It is well known that the vascular tone of small arteries (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, moderate global dietary restriction during gestation in the rat leads to hypertension which is more pronounced and develops earlier in male offspring (Ozaki et al 2001) and liver and cholesterol alterations are found only in male rats (Howie et al 2012). Whether this sexual dimorphism is related to perinatal programming itself or to the later protection of female sex hormones (Grigore et al 2008, Jones et al 2012 is still under debate. Our data showing identical alterations in MUN and POF males and females before sexual maturity support a later protective role of female sex hormones, as previously suggested.…”
Section: Sex-dependent Effectsmentioning
confidence: 99%
“…Our data showing identical alterations in MUN and POF males and females before sexual maturity support a later protective role of female sex hormones, as previously suggested. For example the fact that hypertension induced in the offspring of rats exposed to placental insufficiency is normalized in females after puberty (Alexander 2003, Jones et al 2012. Moreover, blood pressure is significantly increased following ovariectomy in adult female growth restricted offspring (Ojeda et al 2007).…”
Section: Sex-dependent Effectsmentioning
confidence: 99%